Interpersonal Relationships of students in Junior High School - Khadijah Lubis; Daharnis Daharnis; Yarmis Syukur (International Journal of Research in Counseling and Education, 2019)
In adolescence, the competence of interpersonal relations develops and increase. However, students still face some problems during puberty. These include being ostracized, mocking each other, an unpleasant class atmosphere, isolations, and selfishness. To overcome these problems, guiding and counseling services are needed. Nevertheless, for it to be effective, it is important to understand students' interpersonal issues accurately. The purpose of this study therefore was to describe the nature of interpersonal relationships among students in junior high school. The sample population consisted of 133 junior high school students selected by proportional random sampling technique. Furthermore the instrument used is the scale of interpersonal relations with reliability 0.881. Data analysis used a quantitative approach with descriptive methods. The results therefore showed interpersonal relationships among students were advanced, having an average score of 206.77 and anachievement rate of 78%. The findings of this study might be used by counselors to improve students' interpersonal relationships.